Can cereals be bred for increased selenium and iodine concentration in grain? - Lyons, G; Ortiz-Monasterio, I; Genc, Y; Stangoulis, J; Graham, R (MTT, 2005)
Selenium (Se) and iodine (I) are essential micronutrients for humans and animals, and deficient and marginal intakes are widespread. Staple cereals with superior ability to take up these elements from the soil and load them into grain have the potential to improve the Se and I status of whole populations. In this study, diverse cereal germplasm from surveys and field trials conducted in Australia, Mexico, Nigeria and the USA, was evaluated for genotypic variation in grain density of Se and I. Much of the variation in grain Se density was associated with spatial variation in soil available Se, particularly in South Australia. No significant genotypic variation was detected in grain Se density among modern commercial bread or durum wheat, maize, triticale or barley varieties. However, the diploid wheat, Aegilops tauschii L. and rye were higher than other cereals in field and hydroponic trials. No genotypic variation was detected in grain I concentration in the wheat or maize cultivars tested. Se was more evenly distributed throughout the grain of wheat than rice. Although concentrations of available Se and I in soil are the most important determinants of levels of these micronutrients in cereal grain, there may be sufficient genotypic variability in Se and I density in rice to enable selection for these traits. Further evaluation of diverse rice germplasm grown together on various soil types is needed to confirm this. Given that substantial Se and I (particularly I) are lost during polishing, screening programs should investigate possible genotypic differences in grain distribution of these micronutrients, with selection for greater concentration in the endosperm a primary criterion.
Keywords: Ka; genotypic variation; iodine; maize (Zea mays L.); rice (Oryza sativa L.); rye (Secale cereale L.); selenium; wheat (Triticum aestivum )